Evaluation of the Performance of the Roraya I Irrigation Network in Baito District in South Konawe Regency - Didi Saputra, Eka; Lakawa, Irwan; Sulaiman, Sulaiman; Syamsuddin, Syamsuddin (Sultra Civil Engineering Journal (SCiEJ), 2023)
Development and management of irrigation networks requires good infrastructure so that it will support increased food production, improve community welfare and optimize the use of water resources. The purpose of the study was to analyze the performance of the physical infrastructure irrigation system in the Roraya I Irrigation Area, and to analyze the handling of the physical infrastructure irrigation system performance in the Roraya I Irrigation Area The results of the analysis of the performance of irrigation networks on physical infrastructure are lacking and need attention, with a weight value of 59.44%, and for handling irrigation networks on physical infrastructure in the form of maintenance that is heavy repair or replacement